Outcomes of elderly hip fracture patients in the Swiss healthcare system (Swiss Medical Weekly, 2010)
Problem and questions: The consequences for elderly patients with hip fractures are well known. In Switzerland, the introduction of diagnosis related groups (DRG) will bring additional challenges. New models of care, such as Geriatric Fracture Centres (GFC), may be the key to minimising negative outcomes. This study documents outcomes of hip fracture patients in the Swiss healthcare system, for use as baseline data prior to DRG- and GFC-implementation, and compares them to results reported in the literature, for example by Cooper (1997). Methods: This was a prospective cohort quality assurance survey with a one-year follow-up. Outcomes were mortality, living situation, required support and mobility. All patients 65 years of age or older with a proximal femoral fracture were included. Data were analysed by descriptive and interferential statistics. Results: From 272 patients, 70% were community dwelling pre-fracture. Overall, one-year mortality was 22%. Pre-fracture community dwelling patients had better outcomes than nursing home patients with a one-year mortality rate of 12%. A total of 83% of pre-fracture community dwelling patients still lived in the community after one year but more needed help with activities of daily living (ADL) or mobility. Patients with dementia, ADL- and mobility dependency pre-fracture were significantly more at risk for being newly admitted to a nursing home. Conclusions: Our results reflect the clinical reality of the hip fracture population in Switzerland. Results one year after fracture were comparable to study findings in different health care systems. Our findings provide important baseline data prior to the implementation of DRG and GFC.